Hubungan Dukungan Orang Tua dengan Motivasi Belajar Anak Usia Dini di KBIT Al-Islah - Mita Sari; Nur Risha Djumaat; Nurlatifa Olola; Naswa Ramadani Mamonto; Aida Insani Azzahra; Rahmayanti Datunsolang; Nur Nabila Pathan; Amaliatu Khairah Latif; Siti Muzdalifa Uaneto; Revalina Mokoagow; Ni Luh Putriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to examine in depth the relationship between parental support and early childhood learning motivation. The study used a quantitative method with a survey approach involving five sample families with early childhood children in a PAUD environment. Data collection was conducted through a questionnaire designed to measure the level of parental support, including emotional, cognitive, and material support, as well as the level of children's learning motivation. The results showed that parental support has a positive and significant relationship with early childhood learning motivation. Emotional support, such as attention, affection, and positive encouragement, helps children feel safe and confident in learning activities. Cognitive support in the form of learning assistance and intellectual stimulation encourages children to be more active and enthusiastic in the learning process. In addition, material support, such as the provision of adequate learning facilities, also contributes to increasing children's interest in learning. Overall, parental support has been shown to increase children's self-confidence, commitment, and enthusiasm for learning. The implications of this study emphasize the importance of active parental involvement in supporting children's learning processes from an early age to achieve optimal and sustainable learning outcomes.